Synthesis and Physico-Chemical Properties of Zinc Aluminium-Layered Double Hydroxide and Its Nanocomposites - Mamat, Mazidah (2008)
In this study, zinc-aluminium-nitrate-LDH (ZANO) at different Zn/Al molar ratios of 1, 2, 3 and 4 were successfully synthesised via co-precipitation method. Studies on intercalation of various anions namely dodecylsulphate (DS), acetate (AC), anthranilate (AN), salicylate (SAL) acetylsalicylate (ASAL), 2,4-dichlorophenoxy acetate (24D), naphthalene acetate (NAA) and anthraquinone-2-sulfonate (AQ2) for the formation of the nanocomposites had been carried out. The anions of DS (having 12 C) and AC (having 2 C) were chosen to study the effect of the alkyl length on the formation of the nanocomposites and it was revealed that the basal spacing values were varied depending on the size of the anion. The nanocomposites of AN, SAL and ASAL with different ortho benzoate substitution groups were prepared via co-precipitation method. The basal spacing expansions of the nanocomposites: ZAA (ca. 1.3 nm), ZAS (ca. 1.6 nm) and ZAAS (1.6 nm) compared to that of the LDH (0.9 nm) are evidence of the successful intercalation process. Anion exchange study of various anions having different number of benzene rings (24D, NAA, AQ2) and different ortho benzoate substitution groups (AN, SAL, ASAL) were carried out. ZADS was chosen as a starting material where DS (interlayer anion), was expected to exchange with the newly introduced anions. Only AQ2 and AN were successfully exchanged with DS in between the layers. Thermal decomposition of the nanocomposites (ZAA, ZAS, ZAAS) at the heating temperature of 100-1000 ºC showed that the nanocomposites were thermally stable up to 300 ºC. The release profile of the ASAL anion from ZAAS in different solutions (pH 2, 6.5, 10) revealed that the ASAL anion was rapidly released into the medium at pH 2. The interlayer spacing of ZAAS slightly reduced at pH 6.5 and at pH 10 the basal spacing shrinks due to the replacing the ASAL anion by the carbonate anion. Kinetic models of pseudo-second order could be used to describe the release of the ASAL from ZAAS.